The Impact of Covid-19 on the Income of Fishermen Processing Anchovy (Stolephorus sp) in Hajoran Village, Pandan Subdistrict, Central Tapanuli Regency North Sumatra Province - Pasaribu, Herpina; Warningsih, Trisla; AN, Darwis (Faculty of Fisheries and Marine, Universitas Riau, 2023)
The Covid-19 pandemic in Indonesia occurred in March 2019. The implementation of social and physical distancing has disrupted the economy, one of which is the fisheries sector. One example of the impact on the economic sector is the reduced income of fishermen's families, including anchovy processing fishermen in Hajoran Village. The purpose of this study was to analyze the impact of Covid-19 on anchovy income and marketing before and after the pandemic in Hajoran. This research was conducted from 21 June to 30 June 2022 in the Hajoran Village. The method used is a survey. Anchovy fishermen consist of 46 people. The research data were obtained through direct observation and documentary interviews. Based on the results of the analysis, it is known that both before and after the Covid-19 pandemic had an impact on the income of anchovy processing fishermen, where the average income before the pandemic was IDR 238,913 and after the pandemic was IDR 1,213,043. Apart from that, the Covid-19 pandemic also had an impact on the marketing of anchovies, where before the pandemic the price of anchovies was IDR 60,000/Kg while during the Covid-19 it was only IDR 30,000/kg.